Dialectical method and systematization: mediations in training and professional work (Temporalis, 2026)
The article aims to reflect on the systematization of social workers’ professional work based on the dialectical method, understanding it as a constitutive dimension of both work and critical education. This qualitative and exploratory study employs bibliographic and documentary research, as well as the analysis of plans and products derived from systematizations developed within a didactic-pedagogical experience, seeking to highlight the articulation between theory and practice. Based on an examination of the ontological and epistemological foundations of Marx’s method, the study demonstrates that systematization — as a process of apprehending and interpreting social reality — has the potential to enhance professional intervention and give greater visibility to professional work. The discussion also considers the current scenario of work intensification in the contemporary phase of capitalism, marked by financialization and platformization, as well as the implications of this context for social workers and for the exercise of systematization. The findings suggest that the dialectical method, as the foundation of systematization, strengthens the critical analysis of reality and reinforces the ethical-political project in both professional training and professional work.
Keywords: Dialectical Method; Professional Training; Professional Work; Systematization of Practice